The recent ecological efficiency development in China: interactive systems of economy, society and environment - Yang, Rui; Wu, Shaomin; Wong, Christina W. Y.; Liu, Kaiyuan; Miao, Xin; Chen, Yingwen; Wang, Sisi; Tang, Yanhong (Technological and Economic Development of Economy, 2023)
Ecological efficiency (EE) provides much reference for formulating appropriate regional economic, social and environmental policies to promote sustainable development. Interactive subsystems of economy, society and environment within EE system have been considered in this paper. By innovatively integrating the merits of two advanced economic research methods (global super efficiency network data envelopment analysis (GSE-NDEA) and panel vector autoregression (PVAR) and updating the EE evaluation indicator system by following the new features of sustainable development in the recent China, this paper comprehensively evaluates EE by drawing evidence from 3 regions in China during the period of 2011–2020, and further reveals how the three subsystems within EE system interact to achieve EE enhancement. The findings show EE and its three subsystems’ trend, the major constrains of EE development, the regional discrepancies in EE progress, and the interactions among the subsystems of economy-society-environment within the EE system in different regions of China. The policy implications are proposed accordingly.First published online 15 November 2022